Modern Age Learning: Understanding the Modifications of Teaching and Learning Styles (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
Education can be defined as the acquisition of knowledge, skills, values, morals, beliefs,  habits, and personal development. It can be further considered as an experience that has a formative effect on the way one thinks, feels, or acts. There has been much interest andmodification in learning modalities and styles over the last two decades. Few of the facile method floated up, such as the autodidacticism; evidence-based learning, blended learning, self-assessment, which are coined by many pedagogical researchers to beadopted in present learning environment. The field of Online and Open Education is considered for this research, which identifies the works of curriculum development including the methods of teaching and students' engagement as a process of establishingthe understanding of certain educational norms catering to larger values and economic support. This aims to upgrade the current methods of study for students and professionals enrolled in the academic and industrial structures and wish to upgrade their learnings with time. Hence, the researcher examined the curricular developments in the recent decades to search out the theoretical and pedagogical bases of blended and distance education systems. The analysis of the new trends and concepts that have evolved, formed a basis of consideration to curate content and delivery method. Further, the new possible methodssuch as the use of computer software, videos, animations, and interactive sessions were encouraged into the learning processes, by the respondents of a survey under this research. The study consolidates with development of interactive content as a mode ofdelivering education and instruction on an individual basis to learners who are not physically present in a traditional setting such as a classroom. Modernization has brought up a remodelled idea of education with the with the more specific purpose of developingindependent thinking in the learner. The research implies to the social purpose and personal development that had long been the two principal aims of educational systems. These changes attempted to meet the needs of a free society, of a society becomingculturally aware of itself and of the specific manpower requirements of a modern society, further assisting the identification of modified pedagogical methods that may be adopted by academicians.